Pengaruh Etos Kerja, Kompetensi Kerja, Motivasi Kerja, Dan Pengalaman Kerja Terhadap Kesiapan Kerja Mahasiswa Program Studi Manajemen Angkatan 2021 Universitas Sarjanawiyata Tamansiswa Yogyakarta - Tasya Adelia, Salsabila; Prayekti, Prayekti; Lysander, Mohammad Ahyar Syafwan (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study aims to determine the effect of work ethic, competence, motivation, and work experience on the readiness of 2021 Management students at Sarjanawiyata Tamansiswa University Yogyakarta. The population was 253 students, with a sample of 72 respondents determined using the Slovin formula. The sampling technique used accidental sampling. Data quality test analysis using validity and reliability tests. Data analysis techniques using classical assumption tests, including normality tests, multicollinearity tests, and heteroscedasticity tests. Hypothesis testing using f test, t test and coefficient of determination (R2). The results showed that work ethic and work experience have a positive and significant influence on work readiness. Meanwhile, work competence and work motivation have a positive and insignificant influence on work readiness. These findings strengthen the theory that work ethic and experience are very important in preparing students for the world of work. The implication of this research is to improve a disciplined and dedicative work ethic, and work experience from internships also enriches students' practical insights. These results are expected to be the basis for developing more targeted policies and academic programmes to face the competitive world of work.